2020
DOI: 10.1021/acs.est.0c04204
|View full text |Cite
|
Sign up to set email alerts
|

Deep Nitrate Accumulation in a Highly Weathered Subtropical Critical Zone Depends on the Regolith Structure and Planting Year

Abstract: Nitrate accumulated deep (>100 cm) in the regolith (soil and saprolite) threatens groundwater quality, but most studies focus only on nitrate nearer the surface (<100 cm). Surface soil management versus regolith interactions affect deep nitrate leaching, but their combined impact remains unclear. This study measured how deep nitrate accumulation was affected by crop practices including orchard/cropland planting years, regolith structure, and soil properties in highly weathered subtropical red soils. Deep nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 74 publications
0
21
2
Order By: Relevance
“…Liu et al 14 showed that the mean nitrate accumulation in 0−6 m soil profile in 25-year-old apple orchards in the Loess Plateau was 7250 kg N ha −1 . Compared to the studies at other regions, 15,21,35 nitrate accumulated in soil profiles of orchards in the Loess Plateau was very high. The main reason is that overapplication of N is very common in our study region.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…Liu et al 14 showed that the mean nitrate accumulation in 0−6 m soil profile in 25-year-old apple orchards in the Loess Plateau was 7250 kg N ha −1 . Compared to the studies at other regions, 15,21,35 nitrate accumulated in soil profiles of orchards in the Loess Plateau was very high. The main reason is that overapplication of N is very common in our study region.…”
Section: Resultscontrasting
confidence: 74%
“…1,40−43 The denitrification in deep soil profiles at humid subtropical and tropical regions is strong due to high precipitation and high temperature. 44,45 Compared with the studies at subtropical and tropical regions, 15,35 weak denitrification was another reason for the high levels of nitrate stored in the vadose zone in our study region.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…Agricultural soils in tropical regions are far more susceptible than soils in other parts of the globe to carbon mineralization and its knock-on impacts to a range of important soil properties. This is particularly the case for red soils, which are heavily weathered soils rich in iron oxides that have low cation exchange capacity (CEC), low pH, poor fertility, and are prone to erosion (Yang et al, 2020). These soils are dominant in tropical and subtropical regions across the globe, so their management to improve nutrient and water retention is extremely important for global food security.…”
Section: Introductionmentioning
confidence: 99%
“…China ranks first in the world in intensive agriculture, which requires substantial amounts of synthetic fertilizer to meet the demands for crop growth and yield, and this results in agricultural non-point-source pollution [1,2]. Nitrogen (N) is an essential nutrient for crop yield, and over half of the world's population is nourished by crops grown with N fertilizers [3]. However, only about 42-47% of N added to croplands is converted to crop growth, while the rest remains in soil, often leaching into groundwater following heavy rains or irrigation [4][5][6].…”
Section: Introductionmentioning
confidence: 99%